Penerapan Teknologi Tepat Guna untuk Meningkatkan Kinerja Produksi dan Mutu Simpan Produk Bandeng - Kusumastuti, Sri; Suryono, Suryono; Artha Rochmanto, Raditya; Setya Kartika, Vinda; Rizal, Aminuddin (J-Dinamika : Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the food processing sector play a strategic role in supporting local economies but often face limitations in production technology and packaging systems. Griya Bandeng Sukati is a milkfish processing MSME in Semarang with promising products, yet its production process relies on manual seasoning preparation and conventional packaging. Manual seasoning requires considerable time and labor while producing inconsistent quality. In addition, non-vacuum packaging limits product shelf life and market expansion. This community service program aims to improve production performance and product shelf life through the application of appropriate technology in the form of a food chopper and a vacuum sealer. The implementation method includes problem identification, equipment procurement and testing, training on operation and maintenance, and continuous mentoring and evaluation. The results indicate that the food chopper significantly improves production efficiency and seasoning consistency, while the vacuum sealer enhances packaging quality and extends shelf life. Training and mentoring enable the partner to operate the equipment independently. Overall, the program positively impacts productivity, product quality, and MSME competitiveness.